Pengaruh Struktur modal, free cash flow dan profitabilitas terhadap manajemen laba pada perbankan syariah yang terdaftar di bursa efek Indonesia periode 2020-2021 - Alafiyah, Nur Alif (ITB AAS INDONESIA Surakarta, 2024)
The aim of this research is to analyze the influence of capital structure, free cash flow and profitability on earnings management. This research is associative quantitative research which aims to determine the relationship between two or more variables, looking for roles, influences and causal relationships, namely between the independent variable and the dependent variable. The object of this research is sharia banking listed on the Indonesian stock exchange in 2020-2023, consisting of Bank Syariah Indonesia, Bank Aladin Syariah, BTPN Syariah and Panin Dubai Syariah. The analytical method used is multiple linear regression analysis models. The results of this research show that capital structure (DER) partially has a significant negative effect on earnings management with a significance value of